Perancangan Interior Cooking Club for Kids di Surabaya - Vania Sutrisno; Cok Gede Padmanaba (Intra, 2016)
Nowadays, cooking is not only favored by adults but children at an early age also begin to develop their talents in cooking. Surabaya is still lack of available places for cooking courses for children. Learning to cook at an early age can be useful to develop children’s skills and creativity. The design of the cooking club aims to develop children’s talents and interest, packaged in educative and fun learning to cook. The cooking club will provide complete facilities ranging from education in cooking, nutrition information centers and restaurant, so adults can be attracted to visit. The method in this design consists of four stages, the first stage is Define (this is a stage of problem analysis and data collection), Ideate (in this stage, the idea of design would answer the problem), Prototype (this stage is a product design), test (this is the stage of design evaluation). The design concept used is creative and healthy smile, which can enhance children's creativity in learning how to cook healthily and happily.